2019
DOI: 10.1007/s10639-019-10059-5
|View full text |Cite
|
Sign up to set email alerts
|

Matching self-reports with electrodermal activity data: Investigating temporal changes in self-regulated learning

Abstract: This study investigated the interplay of temporal changes in self-regulated learning processes (i.e., behavioral, cognitive, motivational and emotional) and their relationship with academic achievement in computer-supported collaborative learning. The study employed electrodermal activity and self-report data to capture the dynamicity of selfregulated learning processes during 15 sessions of collaborative learning activities. Our findings revealed that the changes in motivational regulation was related to acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 57 publications
2
20
1
Order By: Relevance
“…First, not all studies systematically manipulated CL according to CLT (Morton et al, 2019). Second, the majority of studies did not combine physiological data with self-reported CL (Dindar et al, 2019;Larmuseau et al, 1552British Journal of Educational Technology Vol 51 No 5 2020. Moreover, it might be interesting to link physiological data with task performance across the different sets of exercises, as previous studies indicated that physiological adjustments ensure that task performance remains the same across different levels of complexity (Brouwer et al, 2014;Iani, Gopher, & Lavie, 2004).…”
Section: Shortcomings and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, not all studies systematically manipulated CL according to CLT (Morton et al, 2019). Second, the majority of studies did not combine physiological data with self-reported CL (Dindar et al, 2019;Larmuseau et al, 1552British Journal of Educational Technology Vol 51 No 5 2020. Moreover, it might be interesting to link physiological data with task performance across the different sets of exercises, as previous studies indicated that physiological adjustments ensure that task performance remains the same across different levels of complexity (Brouwer et al, 2014;Iani, Gopher, & Lavie, 2004).…”
Section: Shortcomings and Research Questionsmentioning
confidence: 99%
“…First, most studies did not systematically manipulate CL based on insights from CLT (Morton et al, 2019). Second, the majority of studies did not combine physiological data with self-reports and task performance (Dindar, Malmberg, Järvelä, Haataja, & Kirschner, 2019;Larmuseau et al, 2019). Third, there is no unambiguous answer to which physiological features are best in assessing CL (Larmuseau et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…EDA has recently been used to observe emotions during educational processes like self-regulated and multimedia learning (Dindar et al, 2019;Mudrick, Taub, Azevedo, Price, & Lester, 2017) and reading (Meer, Breznitz, & Katzir, 2016). Dew et al (1984) used various measures of EDA and different scales to assess MAtrait and MAstate, but found no relation between EDA and MAstate, and only a small relation between EDA and MAstate for one of their measures of EDA.…”
Section: Assessing Mathematics State Anxietymentioning
confidence: 99%
“…For example, an individual can be highly interested in working on a problem‐solving task with their teammates, but their task interest may decrease towards the end of the task if the task is too difficult or if the individual cannot get along with their teammates. Given the dynamic nature of metacognitive experiences, a common approach when studying them has been to assess them with single‐item self‐reports at multiple time points during a learning task (Dindar, Malmberg, Järvelä, Haataja, & Kirschner, 2020).…”
Section: Metacognitive Experiencesmentioning
confidence: 99%
“…Furthermore, negative group emotions were found to contribute to higher PS. Dindar et al ., (2020) investigated the PS of students in a high school physics course over a term. The course was composed of collaborative learning and problem‐solving sessions.…”
Section: Ps As An Indicator Of Cps Processesmentioning
confidence: 99%